Religious Moderation in the Perspective of Madrasah Tsanawiyah Teachers - Minabari, Khalid Hasan; Kamaludin, Nurain; Miraj, Safri; Rachim, Zaitun A. (Universitas Negeri Semarang, 2024)
This study discusses the implementation of the religious moderation program in private Aliyah Madrasah in Lebak Regency, Banten Province. The purpose of this study is to describe the implementation of religious moderation policies, identify strategies for the implementation of religious moderation policies, and identify supporting and inhibiting factors for the implementation of religious moderation by teachers at Madrasah Aliyah Nurul Hidayah Lebakjaha and Madrasah Aliyah Daar El-Ishlah Malingping, Lebak Regency. This study uses a descriptive qualitative approach with observational data collection methods, interviews, and documentation. The stages of data analysis include data reduction, data presentation, and data verification, while checking the validity of data is carried out by expanding participation, accuracy of observation, triangulation, and consultation with supervisors. The results of the study show that: (1) The implementation of the strategy to strengthen religious moderation in madrassas has been integrated with the values of religious moderation through teaching and learning activities (KBM), extracurricular activities (SKI), and habituation activities. (2) The strategy to strengthen religious moderation in Madrasah is an effort made by the head of the madrasah, namely: (a) Persuasive approach, (b) Deideologizing teachers who are exposed to extreme understanding, (c) Integrative policy of religious moderation, (d) Synergizing learning programs with activities outside of learning, and supporting factors for the implementation of religious moderation in madrasas include: Vision and mission of the madrasah, madrasah regulations, community interest, The atmosphere of the madrasah is conducive, infrastructure facilities, motivation for achievement, and academic qualifications of supervisors, while the inhibiting factors are inadequate library conditions, social media/mass, community environment, and family environment. The implementation of the religious moderation program at the private Aliyah Madrasah in Lebak Regency has shown positive results. The strategies implemented by the head of the madrasah and the existing supporting factors have helped in integrating the values of religious moderation into learning activities and madrasah life. However, there are still several inhibiting factors that need to be overcome to increase the effectiveness of religious moderation programs in madrassas.